ЖАНУБИЙ ОРОЛ БЎЙИДАГИ МАДАНИЯТ, МАЪНАВИЯТ ВА МАЪРИФАТНИНГ ЧУҚУР ИЛДИЗЛАРИ. - Хожаниязов, Ғ.; Юсупов, О.; Календаров, У. (SCIENCE and SOCIETY, 2016)
The article deals with the origin and foundation of the historical-natural museum in Karakalpakstan in the 20-30-th of the XX-th century on the basis of archive materials and scientific literature. The Karakalpak natural museum was the spiritual – educational centre of social life, the scientific – pedagogical work of Karakalpak regional department of public education. The specialists from scientific centres of Uzbekistan helped very much in the foundation of Karakalpak historical – natural museum.
Keywords: South coast of the Aral sea; rare archaeological objects; Toprak Kala; Kiyat Kala; Guldursyn Kala; rare heritage; Karakalpak natural museum; Uzbek natural society; Karakalpak ethnographic expedition; Karakalpak historical and natural museum